Pelaksanaan Kawin Lari dan Akibat Hukumnya di Tinjau dari Hukum Adat Batak Angkola (Studi di Desa Sibangkua) - Sandi Saputra Ritonga; Bandaharo Saifuddin; Marwan Busyro (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the practice of elopement (kawin lari) and its legal consequences from the perspective of Batak Angkola customary law, as well as its relation to Law Number 1 of 1974 on Marriage. The research was conducted in Sibangkua Village, Angkola Barat District, South Tapanuli Regency. The method used is an empirical legal approach, with data collected through observation and interviews with traditional leaders, religious figures, village officials, and individuals involved in elopement. The findings reveal that elopement frequently occurs in Batak Angkola society, mainly due to high dowry demands, disapproval of arranged partners, or violations of social and religious norms. The resolution process is carried out through customary stages such as mandokon ulang agoan, marsapa adat, and patibal sere. Although the national marriage law does not explicitly regulate elopement, it is recognized within Batak Angkola custom and has a structured resolution mechanism. Nevertheless, socially, elopement is often viewed negatively and may damage the family’s honor.